ADDIE SEBAGAI MODEL PENGEMBANGAN MEDIA INSTRUKSIONAL EDUKATIF (MIE) MATA KULIAH KURIKULUM DAN PENGAJARAN - Nyoman Sugihartini; Kadek Yudiana (Universitas Pendidikan Ganesha, 2018)
Curriculum and teaching courses do not have learning media that can support the implementation of blanded learning. This study aimed to: design and implement Educative Instructional Media courses in Curriculum and Teaching. The development model used is the ADDIE model consisting of five stages: 1) analysis, 2) design, 3) development, 4) implementation and 5) evaluation. In the analysis phase, analysis is done related to the needs of the system and the analysis of learning objectives curriculum and teaching courses in accordance with the syllabus. Based on the analysis of the material was divided into 7 chapters. At the design stage, a systematic design of curriculum and teaching modules is carried out and the system, database, and interface design stages are carried out. Development stage is the continuity of what has been designed, compiling the content in accordance with the syllabus, in this case LMS (Learning Management System) used Moodle. The implementation phase is to enter content into Moodle by presenting the learning process following the stages of the project based learning (PjBL) model.